Inhibition of CYP2E1 With Propylene Glycol Does Not Protect Against Hepatocellular Injury in Human Acetaminophen Daily‐Dosing Model. (27th August 2018) - Ganetsky, Michael; Berg, Anders H.; Solano, Joshua J.; Salhanick, Steven
Abstract: Acetaminophen (APAP)‐induced liver injury is initiated by metabolism of APAP by the cytochrome P‐450 (CYP) system, primarily CYP2E1. We previously demonstrated CYP inhibition following administration of a liquid APAP formulation containing propylene glycol, a CYP2E1 inhibitor, and other excipients. This study was undertaken to determine if propylene glycol specifically inhibits production of CYP‐derived metabolites and if propylene glycol reduces the rise in alanine aminotransferase (ALT) seen following prolonged APAP dosing. Human subjects were randomized to receive 4 g of APAP daily in one arm of the study or 4 g of APAP with 5 mL of 99% propylene glycol in the other arm, both for 14 days. After a washout period of at least 14 days, subjects were crossed over between arms. Outcomes were rise of ALT greater than 2 times baseline (responders) and proportion of randomly sampled CYP‐derived metabolites relative to total metabolites produced. There was no difference in percentage of responders between treatment groups: 6 of 21 in the APAP group (29%) compared with 8 of 20 in the APAP + propylene glycol group (40%); chi‐square, P  = .59. For all subjects, the mean percentage of CYP‐derived metabolites produced was 5.8% (APAP) versus 4.3% (APAP + propylene glycol); P  = .018. This effect was solely attributable to the responders: the mean percentage of CYP metabolites of responders was 7.7% (APAP) versus 4.6% (APAP + propylene glycol), P  = .050, whereas there was no difference for the nonresponders. Five subjects were responders in both arms (2% probability of random occurrence). Our data indicates that propylene glycol inhibits CYP2E1 metabolism of APAP in some subjects but does not effect hepatocellular indury at the dose given.